Potential role of lncRNA cyp2c91–protein interactions on diseases of the immune system - Suravajhala, Prashanth; Kogelman, Lisette J. A.; Mazzoni, Gianluca; Kadarmideen, Haja N. (Frontiers in Genetics, 2015)
With unprecedented increase in next generation sequencing (NGS) technologies, there has been a persistent interest on transcript profiles of long noncoding RNAs (lncRNAs) and protein-coding genes forming an interaction network. Apart from protein-protein interaction (PPI), gene network models such as Weighted Gene Co-expression Network Analysis are used to functionally annotate lncRNAs in identifying their potential disease associations. To address this, studies have led to characterizing transcript structures and understanding expression profiles mediating regulatory roles. In the current exploratory analysis, we show how a lncRNA - cyp2c91 contributes to the transcriptional regulation localized to cytoplasm thereby making refractory environment for transcription. By applying network methods and pathway analyses on genes related to a disease such as obesity and systemic lupus erythematosus, we show that we can gain deeper insight in biological processes such as the perturbances in immune system, and get a better understanding of the systems biology of diseases.